Effect of carbamazepine and levetiracetam on coagulation parameters: Prothrombin time, activated partial thromboplastin time, D-dimer, and fibrinogen levels - Li Jiaohui; Zhong Chengyun; Bian Guanji (Journal of Medical Biochemistry, 2025)
Background: Epilepsy is a prevalent neurological disorder, and evaluating its treatment strategies is highly significant. This study aimed to compare the effects of monotherapy with carbamazepine and levetiracetam on the results of coagulation tests, including prothrombin time, activated partial thromboplastin time, fibrinogen, and D-dimer levels, as well as on seizure control in patients with partial-onset epilepsy. Methods: A total of 89 patients diagnosed with POE and treated at our hospital between January 2023 and January 2024 were enrolled. The patients were divided into the carbamazepine group and the levetiracetam group. Blood coagulation parameters, including prothrombin time, activated partial thromboplastin time, fibrinogen, and D-dimer levels, were measured at baseline (before treatment) and at 1, 3, and 6 months after medication initiation. Additionally, the frequency and severity of epileptic seizures were recorded for each group. Results: In the carbamazepine group, prothrombin time, activated partial thromboplastin time, and D-dimer levels were significantly reduced at 1-, 3-, and 6-months post-treatment compared to pre-treatment levels. Conversely, these changes were less pronounced in the levetiracetam group. Fibrinogen levels decreased in both groups after treatment. The frequency of epileptic seizures was markedly reduced in all patients after treatment. There was no significant difference in seizure control rates between the carbamazepine and levetiracetam groups. Conclusions: Carbamazepine may pose a higher risk of coagulation abnormalities but demonstrated strong efficacy in controlling epileptic seizures. Levetiracetam had a milder impact on coagulation parameters while offering comparable effectiveness in seizure management.